Islamic Ornamental Products from Palm-Based Polyurethane Foam - T.I. Tuan Noor Maznee;; H. Nurul Ain;; P.P. Kosheela Devi;; S. Mohd Norhisham;; A. Srihanum;; S.K. Yeong;; A.H. Hazimah;; N.M. Nik Ahmed Mazlan (Universiti Sains Islam Malaysia, 2024)
Palm-based rigid PU can be produced by reacting suitable palm-based polyol with isocyanate in the presence of additives. The process to produce the palm-based polyol has been filed for patent application (PI 20055231). The blended mixture could be poured into a mould of ,desired design to produce moulded decorative rigid PU products. The advantages of the decorative palm-based rigid PU products are that they are structurally strong, dimensionally stable and impervious to moisture. They can be sprayed or painted with the desired colours to give a wood-like or metal like finishing or any other desired design or finishing. This material can be used to replace or used together with the current decorative building material which are casted from cement or gypsum for building construction. The added advantage of this material is that it is light weight and therefore could lower the installation cost. This material also has no nutritional value to insects, or pests and therefore it is not expected to rot or decay under normal circumstances of use.